Assembly of monolayer nanospheres - Lim, Hong Zheng (2019)
Nanomaterials exhibit extraordinary physical and chemical properties owing to their high surface area and unique atomically thin structure. Assembly of nanomaterials into specific pattern is of importance for many applications including nanolithography, nanostructuring and artificial crystal. In this project, polystyrene nanospheres were assembled on water surface using surface tension of water by means of micro-propulsive injection. These polystyrene nanospheres were injected onto the water surface and allowed to assemble freely to form close-pack hexagonal monolayer which are used for metal nanostructure templates. The results of the assembly process would be discussed and accompanied with optical microscope and Scanning Electron Microscope images. The polystyrene nanosphere monolayer assembled was extended to second layer deposition using the same technique as the monolayer. Multilayer nanosphere structures were also constructed via the vertical deposition method. Finally, metal meshes were made utilising the polystyrene nanosphere monolayer as templates.